Soil Saturated Simulation in Embankment during Strong Earthquake by Effect of Elasticity Modulus. (1st July 2014) - Gordan, Behrouz; Adnan, Azlan; Aida, Mariyana A. K.
Abstract : The dynamic analysis process was started after failure in some embankments during an earthquake. In this context, maximum displacement was reported at the crest based on interaction between structure and reservoir. This paper investigates the dynamic behavior of short embankment on soft soil. For this purpose, numerical analysis was carried out using ANSYS13 program based on finite-element method. Simulated models were vibrated by strong earthquake, so the peak ground acceleration (PGA) and duration were 0.65 g and 5.02 seconds, respectively. The comparison results were discussed in key points of plane strain analysis based on modulus ratio between saturated embankment and foundation. As concluded, the modulus ratio between 0.53 and 0.66 led to having a minimum value of horizontal displacement, relative displacement in vertical direction, and shear stress. Consequently, the shear stress was increased while the modulus ratio was decreased. Finally, to avoid more rigidity in the embankment on the soft soil, optimum modulus ratio was recommended at 0.66 in order to reduce the probabilistic of body cracks at the crest with respect to homogeneous behavior during an earthquake.